A pós-história e as composições imagéticas e sonoras em Vilém Flusser - Valéria Ramos de Amorim Brandão (2021)
The main objective of the thesis entitled “The post-history and the imagetic and sound compositions in Vilém Flusser” is to examine the constitution of the Flusserian concept of post-history (its origins and developments) and the understanding of how the characteristic conformations of this ambience denote a type of being, to be and to do in the world that corroborate to the perception that, the human condition is a simple project in symbiotic development with the world of life codified by humans themselves. From this ambience, it was attempted to apprehend the role of technical images of digital binary synthesis (a concept similar to plastic, an image sign and or an image composition) and the aesthetic relations of similarity that these preferably establish with the sound signs (equivalent concept music and or sound composition). To sum up, the present paper examine more precisely the works of “The universe of technical images: praise of superficiality of 2008 where a first layer of similarity was identified by the author as existing between sound and imaginary signs that emerges: they originate from the logical-mathematical substrate responsible for the constitution of all information, message available in a computational environment. Subsequently, there was a retreat to publications constituted in the 1960s, more specifically focused on “The Devil’s Story” 1965 - where the philosopher indicated the sound structures and the images that conform the layers of unreality belonging to culture. Finally, he turned to the publication “Language and reality” of 1963 - inaugural essay on Flusserian thought - where the thinker stated that sounds and visualities are opposites pole (but not excluding) constitutive of language, being capable of creating reality.